(untitled) (Journal of Health, Population and Nutrition, 2009)
To achieve maximal protection against vaccine-preventable diseases, a child should receive all immunizations within recommended intervals. Clinic records of 512 Nigerian children were evaluated for timeliness in receiving vaccines and the completion rates of the schedule. About 30% of the children presented after four weeks of age for their first immunization; 18.9-65% of the children were delayed in receiving various vaccines compared to the recommended ages for receiving the vaccines. Only 227 (44.3%) children were fully immunized. Health education and mass mobilization of the community and health workers are recommended to improve the uptake of vaccines and to encourage timely receipt of vaccines. Key words: Immunization; Timeliness; Vaccination; Nigeria doi: 10.3329/jhpn.v27i3.3381 J Health Popul Nutr 2009 Jun;27(3):391-395